Model predictive current control for a PMSM fed by an indirect matrix converter with torque ripple reduction - Kim, Keon Young; Bak, Yeongsu; Lee, Kyo Beum (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2019)
This paper proposes a model predictive current control (MPCC) for a permanent-magnet synchronous motor (PMSM) fed by an indirect matrix converter (IMC) for torque ripple reduction. The IMC is used as AC to AC converter of the PMSM drive system. In this paper, the proposed MPCC considers split voltage vectors instead of eight switching states as candidates for cost function optimization. Therefore, the current ripple and torque ripple of the PMSM are reduced considerably in steady state. The computation burden which can be induced from split voltage vectors is diminished in this paper through the computation time reduction technique in a deadbeat fashion. In addition, a grid-side of the IMC is operated through the simple modulation technique which has unity power factor controllability. The performance of the proposed MPCC for reduction of a torque ripple in the PMSM fed by the IMC is verified by simulation results.
Keywords: Computation burden; Cost-function optimization; Indirect matrix converter; Indirect matrix converter (IMC); Model predictive; Modulation techniques; Permanent Magnet Synchronous Motor; Torque-ripple reduction; Indirect matrix converter; Model predictive current control; Permanent-magnet synchronous motor; Torque ripple reduction